2013
DOI: 10.1155/2013/940830
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Supplementation Improves Affective and Motor Behavior in Mice after Radiation Exposure

Abstract: Currently, NASA has plans for extended space travel, and previous research indicates that space radiation can have negative effects on cognitive skills as well as physical and mental health. With long-term space travel, astronauts will be exposed to greater radiation levels. Research shows that an antioxidant-enriched diet may offer some protection against the cellular effects of radiation and may provide significant neuroprotection from the effects of radiation-induced cognitive and behavioral skill deficits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Supplementing diets high in antioxidants have shown to improve the excitatory post synaptic potentials (EPSP) and reversed the impairment of synaptic plasticity induced in dentate gyrus by neurotoxic agents (Karimi et al, 2013). Similarly, C57BL/6 mice maintained on an antioxidant rich pomegranate diet, and then exposed to proton radiation (2 Gy), had attenuating effects on depression-like symptoms (Dulcich and Hartman, 2013). Parallels can be drawn from the current results to suggest that the components of blueberry and strawberry diets, such as antioxidant polyphenols, anthocyanins, phenolic acids and many other bioactive components, synergistically reduce the pro-oxidant load in critical regions of the brain, at the same time up-regulating endogenous antioxidant defenses and activating autophagy.…”
Section: Phf-tau-frontal Cortexmentioning
confidence: 99%
“…Supplementing diets high in antioxidants have shown to improve the excitatory post synaptic potentials (EPSP) and reversed the impairment of synaptic plasticity induced in dentate gyrus by neurotoxic agents (Karimi et al, 2013). Similarly, C57BL/6 mice maintained on an antioxidant rich pomegranate diet, and then exposed to proton radiation (2 Gy), had attenuating effects on depression-like symptoms (Dulcich and Hartman, 2013). Parallels can be drawn from the current results to suggest that the components of blueberry and strawberry diets, such as antioxidant polyphenols, anthocyanins, phenolic acids and many other bioactive components, synergistically reduce the pro-oxidant load in critical regions of the brain, at the same time up-regulating endogenous antioxidant defenses and activating autophagy.…”
Section: Phf-tau-frontal Cortexmentioning
confidence: 99%
“…Some of the studies found adult neurogenesis was arrested completely after brain irradiation ranging from 3 Gy to 20 Gy; and behavioral as well as cognitive impairments were noted as well [13-16]. Some of these impairments include deficits in sensorimotor function [17], novel object recognition tasks [18], associative learning [19], and reversal learning [20]. Hippocampal-dependent spatial memory deficits may be related to a disruption in neurogenesis [13] that could contribute to longer-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the authors suggested that proton radiation may not be as deleterious as HZE particles. Dulcich and Hartman also found no spatial learning and memory deficits in mice 2 months after exposure to a single 2 Gy dose (3). Another study observed no differences between control rats and those given 4 Gy proton radiation in a bar press task that assesses changes in reinforcement contingencies (4).…”
mentioning
confidence: 96%